Determining X-Ray Effective Energy in Linear Accelerator (LINAC) Radiotherapy Instrument - Fauziah, Fauziah; Abdullah, Bualkar (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
This research in determining x-ray effective energy in linear accelerator (Linac) radiotherapy device was done using copper plates at different thicknesses by determining the Half Value Layer (HVL) for each energy. The purpose of this research is to know the amount of effective energy used in radiotherapy linear accelerator. The results showed that the energy of 6 MeV obtained 2,714 MeV of effective energy at HVL 4,500 mm and at the energy of 10 MeV obtained 4,231 MeV of effective energy at HVL 4,500 mm.